Generative Leadership Scale Development Study - (:unkn) unknown (HACETTEPE UNIV, 2019)
The aim of this research is to develop a valid and reliable scale that includes school principals' generative 06.02.2019 leadership behaviors and the expressions defining these behaviors. As a result of the literature review, the item pool was formed and the scope validity ratios were calculated according to the expert opinion. The draft Accepted: item form was carried out as a pilot scheme to a group of 50 teachers. Final general practice was applied to 10.05.2019 442 teachers. For the validation studies of the scale, the factor loadings of the items of the scale were determined by applying the Exploratory Factor Analysis. First, a four-factor structure emerged, followed by Online First: varimax rotation to obtain a two-factor structure. In this process, a total of 35 items were excluded from the 19.05.2019 scale and a scale with two factors named Revealing Creative Dynamics and Innovation Generating Capacity and consisting of 27 items. Subsequently, Confirmatory Factor Analysis was performed and then the study Published: proceeded to reliability analyses and Cronbach's Alpha and Composite Reliability values were calculated. After 31.10.2020 that, the distinctiveness of the scale was examined. Again, using Pearson analysis, the item-total and item-remainder correlations and the correlations between subscales and total scores of the scale items were calculated. All values obtained prove that the scale is valid and reliable.
Keywords: Leadership; leadership types; school principals; generativity; generative leadership; FIT INDEXES